Association of clinical and epidemiological characteristics with COVID-19 BNT162b2 mRNA vaccine short-term adverse reactions in healthcare workers. Issue 12 (2nd December 2021) - Filippatos, Filippos; Tatsi, Elizabeth-Barbara; Dellis, Charilaos; Dessypris, Nick; Syriopoulou, Vassiliki; Michos, Athanasios
ABSTRACT: Introduction: The aim of the study was to investigate the prevalence and severity of adverse reactions (ARs) after immunization of healthcare workers (HCWs) with BNT162b2 vaccine and to associate them with clinical and epidemiological characteristics. Methods: A form containing demographic and clinical data as well as ARs after both doses of the vaccine was completed, and statistical association analysis was performed. Results: A total of 502 HCWs (females 78.3%) with mean age (±SD) 48.17 years (±12.97) participated. After the first dose, 404 (80.5%) HCWs reported at least one local AR (LAR) and 366 (72.9%) after the second dose ( p -value=0.004). After the first dose, 121 (24.1%) HCWs reported at least one systemic AR (SAR) and 275 (54.8%) after the second dose ( p -value<0.0001). In the logistic regression analysis, there was no association of gender or medical history of underlying disease with LARs. There was a negative association of age with the cumulative score (CS) of LARs (OR: 0.82, 95% CI: 0.69–0.96) after the first dose. Females had a positive association with CS of SARs following both doses (OR, 95% CI: 2.57, 1.39–4.73 and 2.71, 1.76–4.19, respectively). Age was negatively associated with CS of SARs (OR: 0.66, 95% CI: 0.57–0.76) after the second dose. Severe ARs included Bell's palsy (1) and tinnitus with temporary hearing loss (1). Conclusion: The administration of the BNT162b2 vaccine in our HCWs cohort had a good safety profile with the most common ARs being self-limited. An increasing rate of SARs following the second vaccine dose was noticed. Rare but severe possible ARs should be further investigated.